2022
DOI: 10.33222/pelitapaud.v7i1.2193
|View full text |Cite
|
Sign up to set email alerts
|

Penanaman Nilai Karakter Cinta Tanah Air Pada Anak Usia Dini Melalui Permainan Tradisional Engklek

Abstract: Permainan tradisional punya potensi yang besar untuk menumbuhkan 18 nilai karakter anak. Penelitian ini bertujuan untuk mendeskripsikan perencanaan nilai penanaman karakter cinta tanah air pada anak usia dini melalui permainan tradisional engklek di TK Khoridatulhuda, untuk mendeskripsikan pelaksanaan nilai penanaman karakter cinta tanah air pada anak usia dini melalui permainan tradisional engklek di TK Khoridatulhuda, serta untuk mendeskripsikan evaluasi nilai penanaman karakter cinta tanah air pada anak usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…Based on the results of this study, it is proven that the Mathematics Ethnic Learning program by utilizing traditional games can effectively increase students' love of the country. This is in line with research conducted by by previous study which states that traditional games can be used as a means to foster a sense of love for the motherland in children (Enok & Mayasarokh, 2022). The results of this study can be concluded that planning begins with entering the eighteen character values into the semester program and then into the RPPM and RPPH.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the results of this study, it is proven that the Mathematics Ethnic Learning program by utilizing traditional games can effectively increase students' love of the country. This is in line with research conducted by by previous study which states that traditional games can be used as a means to foster a sense of love for the motherland in children (Enok & Mayasarokh, 2022). The results of this study can be concluded that planning begins with entering the eighteen character values into the semester program and then into the RPPM and RPPH.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with the Mathematics Ethnic Learning program which was previously implemented by other study which reveals that the program can increase student interest and learning outcomes (Wibowo et al, 2022). Not only improving learning outcomes, but research conducted by other study states that traditional games can be implemented as an effort to increase students' love for their homeland for local wisdom (Enok & Mayasarokh, 2022). Thus, Indonesian culture will not fade and can still be preserved .…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hingga saat ini, untuk memperkuat karakter cinta tanah air telah dilakukan dengan berbagai upaya seperti permainan tradisional engklek yang dapat menumbuhkan kepedulian terhadap lingkungan (Dedeh & Mayasarokh, 2022). Pelatihan terbimbing menggunakan media wayang kertas yang berdampak pada siswa lebih mengenal dan mencintai salah satu budaya tanah air, yaitu wayang kulit (Rozhana dkk, 2022).…”
Section: Pendahuluanunclassified